Growth regime and environmental remediation of microalgae - Hammed, Ademola Monsur; Prajapati, Sanjeev Kumar; Simsek, Senay; Simsek, Halis (The Korean Society of Phycology, 2016)
Microalgal bioremediation of CO2, nutrients, endocrine disruptors, hydrocarbons, pesticides, and cyanide compounds have evaluated comprehensively. Microalgal mitigation of nutrients originated from municipal wastewaters, surface waters, and livestock wastewaters has shown great applicability. Algal utilization on secondary and tertiary treatment processes might provide unique and elegant solution on the removing of substances originated from various sources. Microalgae have displayed 3 growth regimes (autotrophic, heterotrophic, and mixotrophic) through which different organic and inorganic substances are being utilized for growth and production of different metabolites. There are still some technology challenges requiring innovative solutions. Strain selection investigation should be directed towards identification of algal that are extremophiles. Understanding and manipulation of metabolic pathways of algae will possible unfold solution to utilization of algae for mitigation of dissolve organic nitrogen in wastewaters.